Efficacy of Trichoderma asperellum CB-Pin-01 and potassium dihydrogen phosphate to enhance growth and yield and reduce Pythium root rot of hydroponically grown lettuce - Wiraporn Chewapanich; Phraomas Charoenrak; Wanwilai Intanoo; Chiradej Chamswarng (Agriculture and Natural Resources, 2021)
Trichoderma asperellum CB-Pin-01 (Ta) prepared as a fresh culture (Ta-F) and four levels of potassium dihydrogen phosphate (KH2PO4, KP) in concentrated stock nutrient solution B at the normal basal rate (0%, KP-0, 53 g/L) and at 5% (KP-5, 55.65 g/L), 10% (KP-10, 58.3 g/L) and 15% (KP-15, 60.95 g/L) were evaluated for their efficacy to enhance the growth and fresh weight yield of ‘Green Cos’ lettuce grown in a nutrient solution. The results revealed that compared with KP-0, the levels KP-10 and KP-15 significantly increased the fresh weights of the aerial parts (leaves and stem) by 7.45% and 18.21%, respectively, the roots by 38.68% and 22.68%, respectively, and the total plant (aerial parts and roots) by 10.05% and 18.58%, respectively. Treatment with KP-15 supplemented with a spore suspension derived from Ta-F produced the significantly highest plant fresh weight. The two finished bioproducts of Ta (Ta No.1 and Ta No.2) were compared with using Ta-F to control root rot and enhance the growth of ‘Green Cos’ lettuce grown in a nutrient solution infested with Pythium aphanidermatum (Pa). Compared to the non-supplemented control, the KP-15 supplemented with spore suspensions of Ta-F or with the bioproducts Ta No.1 or Ta No.2 significantly reduced the root rot disease index by 50.01%, 47.50% and 22.99%, respectively. The efficacy of Ta No.1 to reduce root rot and increase plant fresh weight, leaf area and root mass volume was comparable to the use of the Ta-F spore suspension. This beneficial fungus colonized lettuce roots, survived at high populations in nutrient solutions and reduced the nitrate accumulation in leaves of hydroponically grown lettuce.